Effects of Bacterial-Feeding Nematodes and Glucose on Phenanthrene Removal by Pseudomonas putida - JING, Yongping; LI, Yan; LIU, Zhaohui; ZHANG, Yingpeng; LIU, Ping; SUN, Ming; LUO, Jiafa (Pedosphere, 2017)
Bacterial-feeding nematodes can promote the bacterial activity through feeding. Bacterial abundance and their activity affect the degradation of polycyclic aromatic hydrocarbons （PAH） such as phenanthrene. The effects of bacterial-feeding nematodes, bacteria, and their interactions on the degradation of phenanthrene with or without glucose were studied through a microcosm experiment. The results showed that up to 57.0% of phenanthrene in mineral medium contaminated with phenanthrene was degraded in the control with bacteria alone and bacteria with the presence of nematodes and/or glucose increased the degradation of phenanthrene by 25.6% to 36.6%. Although both nematode and bacteria abundance decreased gradually, catechol 2,3-dioxygenase （C230） activity increased during the incubation period. Compared with bacteria alone, the presence of nematodes significantly increased C230 activity as well as the abundance of bacteria; this effect was more pronounced when glucose was present. The results imply that nematodes might promote the removal of phenanthrene from medium by stimulating bacteria and C230 activities.